1996
DOI: 10.1016/s0264-410x(96)00117-x
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterisation of a recombinant vaccinia virus expressing human papillomavirus proteins for immunotherapy of cervical cancer

Abstract: The presence and consistent expression of the genes encoding the human papillomavirus (HPV) E6 and E7 proteins in the great majority of cervical tumours presents the opportunity for an immunotherapeutic approach for control of the disease. This report describes the construction and characterisation of a recombinant vaccinia virus designed to express modified forms of the E6 and E7 proteins from HPV16 and HPV18, the viruses most commonly associated with cervical cancer. The recombinant virus (designated TA-HPV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 36 publications
1
73
0
3
Order By: Relevance
“…28,29 Knowledge of the HPV types that are commonly associated with cervical cancers in China allows more precise selection of HPV vaccine development. Such study is crucial for informing policy decisions pertinent to the development of genotype-specific HPV diagnostic probes for and vaccination strategies against HPV infection in Mainland China.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Knowledge of the HPV types that are commonly associated with cervical cancers in China allows more precise selection of HPV vaccine development. Such study is crucial for informing policy decisions pertinent to the development of genotype-specific HPV diagnostic probes for and vaccination strategies against HPV infection in Mainland China.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular immune responses have been reported to be effective for tumor cell destruction and control of HPV infection, as HPV-associated cervical lesions are more prevalent in immunosuppressed patients (30,32). Studies have suggested that cytotoxic T lymphocytes may mediate tumor regression in animal models and protect against persistant viruses (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the safety issue, the domains of the E6 protein required for p53 binding/degradation were mutated or deleted (28,29). The binding site of the E7 protein to the cellular retinoblastoma (Rb) protein was mutated (30). An endoproteolytic cleavage site was introduced between E6 and E7 protein for proper protein folding and better CTL processing.…”
Section: Construction Of a Novel Hpv Type 18 E6 And E7 Consensus-basementioning
confidence: 99%
“…Several approaches have been described for the induction of HPV-specific CTL responses such as immunization with recombinant viruses, HPV-specific proteins or peptides, E7 linked to heat shock proteins or intracellular sorting molecules, peptides/proteins loaded on dendritic cells, DNA-or RNA-transfected dendritic cells (DCs) or cell lines. [8][9][10][11][12][13] We are exploiting the Semliki Forest virus (SFV) expression system. 5,[14][15][16][17] This vector represents an ideal system for the induction of cellular immune responses against the oncoproteins HPV E6 and E7 since, apart from its high efficiency and biosafety, SFV RNA does not integrate and SFV infection is cytolytic by apoptosis.…”
Section: Introductionmentioning
confidence: 99%